‘Ismah And Its Impact On Building The Personality Of The Preacher To God A Doctrinal, Linguistic, And Da‘wah Study/ العصمة النبوية وأثرها في بناء شخصية الداعية إلى الله دراسة عَقَديَّة لغوية دعوية - Mohammed Fahad Alharbi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aims to demonstrate the impact of Prophetic Infallibility (‘Ismah) on building the personality of the preacher (Dā‘iyah) through a doctrinal and linguistic study that highlights the connection between the purity of creed and the clarity of expression in the Prophetic discourse. This research adopts an inductive analytical method by tracing legal texts and statements by scholars related to prophetic infallibility, and analyzing them doctrinally, linguistically, and rhetorically, to reveal their influence in building the personality of preachers and their rhetorical methods, as well as utilizing comparisons to highlight the relationship between the infallibility of meaning and the majesty of expression in prophetic communication. The research clarified that ‘Ismah is not merely a metaphysical attribute but an integrated educational and da‘wah methodology that shaped the personality of the Prophet ﷺ in his speech and actions, making his communication a model to be emulated in the truthfulness of the word, the justice of the discourse, and the gentleness of the style. It also addressed the rhetorical aspect of ‘Ismah in terms of the infallibility of meaning and the sublimity of expression, showing that the Prophetic discourse reached the peak in its purity of content and beauty of expression, and that the faithful preacher emulates it in balancing faith and expression, creed and language.